Facilitating learning by the visually impaired: development and usability evaluation of a specially designed ubiquitous library. Issue 1 (10th March 2021) - Tu, Yun-Fang; Hwang, Gwo-Jen; Lai, Chiu-Lin
Abstract : Purpose: This study aims to develop a ubiquitous library for the visually impaired (ULVI) application (app) and to explore its usability by collecting feedback from visually impaired participants to analyse the problems they might encounter. Their suggestions for improving the app further are also reported. Design/methodology/approach: A total of ten participants were recruited in the study. Ten tasks were assigned for the participants to complete using the ULVI app. The system usability scale was adopted to collect feedback on the app, and interviews were conducted to understand the participants' usage behaviours and perceptions of the app. Findings: The findings indicated that the participants provided positive evaluation of the usability of the app and addressed the functions that might need improvement. Above all, this app was regarded as having great potential. Suggestions and improvements are proposed based on the participants' feedback. Originality/value: In terms of the studies relevant to libraries and the visually impaired, few have evaluated the usability of the ULVI app from the perspectives of the visually impaired users. The ULVI app provides resources for the visually impaired and serves as the foundation for developing a more effective ULVI app.